Low LDL particle levels associate with coronary arteries free from atherosclerosis in long-term type 1 diabetes: the Dialong study - Marte Narum; Jacob Juel Christensen; Kirsten B. Holven; Tore Julsrud Berg; Kari Anne Sveen (Cardiovascular Diabetology)
Abstract Background The risk of developing coronary artery disease (CAD) is increased in type 1 diabetes, due to accelerated atherosclerosis. The molecular mechanisms are yet to be unraveled, but potential functional and quantitative abnormalities in lipoproteins are suggested to be involved. Some individuals have coronary arteries free from atherosclerosis even after living with type 1 diabetes for many decades. We therefore aimed to investigate the associations between a set of lipoproteins and metabolites and the presence of coronary arteries free from atherosclerosis in individuals with long-term type 1 diabetes. Methods Cross-sectional, controlled study of 102 participants with type 1 diabetes and 61 control subjects. We used a high-throughput nuclear magnetic resonance (NMR) spectroscopy platform to quantify circulating lipids and metabolites in serum. In participants without previously established coronary heart disease (CHD) we performed computed tomography coronary angiography (CTCA). Results In the diabetes group, mean age was 62 (7) [mean (standard deviation, SD)] year and diabetes duration 50.6 (4.9) years. Lower particle concentration of all LDL subclass particles associated significantly with higher odds of having coronary arteries free from atherosclerosis (p < 0.05). Low particle concentration of all LDL subclasses also associated significantly with normal Coronary Artery Calcium (CAC) score (p < 0.05 for all), after adjustment for age, sex, BMI, eGFR and statin treatment. The whole diabetes group, independent of presence of CAD, had significantly lower particle concentration of IDL and all LDL and VLDL subclass particles compared to the control group (p < 0.05 for all). Conclusions In this cohort of long-term survivors of type 1 diabetes, lower levels of all types of LDL particles associated significantly with higher odds of having coronary arteries free from atherosclerosis, after adjustment for statin treatment. These results emphasize the importance of early treatment start and lipid management in the development of CAD in type 1 diabetes and suggest a subgroup of long-term survivors of type 1 diabetes to may hold environmental or genetic protective beneficial traits, independent of statin use. More research on the role of lipoproteins in the development of atherosclerosis in patients with type 1 diabetes is needed.